Late 19th and Early 20th Century Urban Net Nutrition by Gender and Race - Scott Alan Carson (Center for Economic Studies and ifo Institute (CESifo), 2023)
Individuals urbanize when the net benefits to urbanization exceed rural living conditions. Body mass, height, and weight are welfare measures that reflect the net difference between calories consumed and calories required for work and to withstand the physical environment. Nineteenth and early 20th century US urban residents had lower BMIs, were shorter, with lower weights than rural residents. Urban net nutrition varied by race, and urban whites and blacks had lower BMIs, shorter statures, and lower weights compared to their rural counterparts. Urban male net nutrition experienced greater variation than urban females, and urban females may not have been affected as much as males by urbanization.
Keywords: C10; C40; D10; I10; N30; 330; urbanization; stature variation; cumulative net nutrition; nativity; race